SUPPORTED LIPID BILAYERS DERIVED FROM ANTIGEN PRESENTING CELLS - Swanberg, Elin (My University, 2016)
The cells in our immune system communicate with each other to describe, and warn about dangerous pathogens, as well as to remember and retain protection against diseases we have already had. These functions are dependent on the system of antigen presentation (AP), where reporting cells (for example dendritic cells and B lymphocytes) gather information and present it to the rest of the immune system to initiate a response. This cell-cell contact, also called an immunological synapse, has been previously studied on supported lipid bilayers (SLBs) where the synapse is triggered on artificially constructed membranes intended to mimic the surface of the AP cells, but lacking the transmembrane proteins and mobility of a cellular membrane. In the last year, a new method of producing SLBs has been presented, where the complexity of the cell membrane is retained by use of native membranes, and the mobility and functions of the transmembrane proteins is preserved by fusion with PEGylated synthetic lipid membranes. The aim of this master’s thesis is to derive native membrane vesicles (NMVs) from the membranes of cells of the immune system, and produce SLBs with the purpose of studying cell-cell interactions with the complex composition of natural membranes, using surface sensitive techniques. The primary technique used in this project is total internal reflection fluorescence (TIRF) microscopy, which has been used to study the formations of SLBs, their fluidity, and to detect antibody labeled complexes on the SLBs. Results from this master’s thesis work show formation of SLBs using NMVs. Retained functions of the membranes are seen as the antigen presenting complex (major histocompatibility complex type II) was detected on B lymphocyte derived SLBs. Furthermore, specific interaction between live T lymphocytes and B lymphocyte derived SLBs were observed. The work in this master’s thesis therefore supports further use of the presented method to study membrane functions of cells by production of SLBs from NMVs. The results from this project also provides foundation to further study cell-cell interactions and membrane functions of the cells of the immune system using the developed methods.
Keywords: Livsvetenskaper; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Annan medicin och hälsovetenskap; Life Science; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Other Medical Sciences